Muscle Synergy for Hand Motions Based on Electromyography Analysis - Zeng, Haibin; Wei, Na; Yue, Shouwei; Tian, Xincheng; Li, Ke (Annual International Conference of the IEEE Engineering in Medicine and Biology Society. IEEE Engineering in Medicine and Biology Society. Annual International Conference, 2018)
This study aimed to investigate the muscle synergy for hand motions of both the left and right hands based on surface electromyography (sEMG) signals. Six hand motions, including hand grasp (HG), four fingers flexion (FFF), index finger extension (IFE), thumb internal rotation (TIR), thumb opposition (TO), key pinch (KP), were examined in the experiment. The sEMG signals were recorded from brachioradialis (BRA), flexor carpi ulnaris (FCU), flexor carpi radialis (FCR), extensor digitorum communis (EDC), flexor digitorum superficialis (FDS), abductor pollicis brevis (APB), first dorsal interosseous (FDI) and abductor digiti minimi (ADM) of both the left and right hands. A co-contraction index (CI) followed by a correlation coefficients (CC) was applied to quantify the muscle synergy during the hand motions and to compare the synergistic patterns across hands. Results shown that the left and right hands had similar muscle synergy (CC (CC>0.9) for any of the motions. For both hands, there were strong correlations between the synergistic matrix of different motions (CC (CC>0.85), including the correlations between HG and FFF, between FFF and IFE, and between TO and KP. By contrast, weak correlations between the synergistic matrix for IFE and that for TIR (CC (CC<;0.1), suggesting a low similarity of the muscle synergy for the two motions. This study shed light on how the muscles of the left and right hands are involved and co-contracted for the dexterous hand motions.